Oak declines: Reviewing the evidence for causes, management implications and research gaps - Rebecca H. Gosling; Robert W. Jackson; Matt Elliot; Christopher P. Nichols (Ecological Solutions and Evidence)
Abstract Oak decline is a complex disorder caused by multiple stressors. Although declines have been observed across Europe since 1700, there is still a lot of uncertainty around the cause, and therefore the appropriate management techniques. Using literature from across European oak ecosystems, this review and perspective discusses the key stressors associated with oak declines in Quercus robur L. and Q. petraea (Matt.) Liebl. in Europe and the newly described acute oak decline breaking out in the United Kingdom (and beyond), with a view to identifying important evidence gaps and management implications. The key factors implicated in oak decline include drought, pests and pathogens. These factors can interact in positive feedback loops to increase stress and decline within oaks. Extreme frost, waterlogging, soil properties, land management, nitrogen pollution, heavy metal pollution, genetic predisposition and mycorrhizal changes could also be involved in decline, but more research is required to understand these. In acute oak decline, necrotic lesions are caused by a bacterial complex of up to three species, and it has been observed that the presence of the wood borer Agrilus biguttatus Fabricius 1776 can amplify the symptoms. Practical implication: The amount that each stressor contributes towards these declines and the ‘tipping points’ are largely unknown and are likely to differ between decline events, sites and even individual trees. This makes management advice provision exceedingly difficult. Historic records show oaks in decline can recover; therefore, allowing trees time and space to recover should be a priority for management practitioners. Future research recommendations for effective management of declining oaks are discussed.